Extending experiential learning in teacher professional development - Tangney, Brendan; Girvan, Carina; Conneely, Claire (My University, 2016)
This paper introduces the use of experiential learning during the early stages of teacher professional development. Teachers observe student outcomes from the very beginning of the process and experience new pedagogical approaches as learners themselves before adapting and implementing them in their own classrooms. This research explores the implementation of this approach with teachers in Irish second level schools who are being asked to make significant pedagogic changes as part of a major curriculum reform. Teachers’ self-reflections, observations and interviews demonstrate how the process and outcomes influenced their beliefs, resulting in meaningful changes in classroom practice.
Keywords: Teacher education; Professional development; Experiential learning; Teacher beliefs; Creative Technologies; Digital Humanities; Education